O Teorema de Fibração de Milnor-Lê - Silva, Camila Sibelle Marques da (2016)
One of the classic tools for the local study of the topology of real and complex analytic singularities is the Milnor Fibration Theorem. In this work, using some fundamental concepts in Singularity Theory, we present a proof obtained by Lê Dũng Tráng of a result that establishes conditions for the germ of a map de ned in a complex analytic subset in Cn to be the projection map of a (locally topologic trivial) bre bundle.